Nanoporosity improves the damage tolerance of nanostructured tantalum nitride coatings. (May 2017) - Xu, Song; Xu, Jiang; Munroe, Paul; Xie, Zong-Han
Abstract: Conventionally, nanostructured ceramics are susceptible to brittle fracture due to processing-induced flaws such as porosity. In this study, the microstructure and deformation behavior of two nanostructured Ta2 N coatings, one with a fully-dense structure and the other with a nanoporous structure, both prepared by double cathode glow discharge technique, were investigated. It was found that the elastic modulus of the Ta2 N coatings is more sensitive to the presence of nanoporosity than their hardnesses. Compared with the fully-dense Ta2 N coating, the nanoporous Ta2 N coating exhibits a marked increase in the damage tolerance, as well as a good potential for wear-resistance. Graphical abstract: